A comparison of aerobic and anaerobic capacities in different positional roles of basketball players aged 13-16 years - Naweepattana, Plaifun; Nantakool, Sothida; Chuatrakoon , Busaba (Journal of Associated Medical Sciences, 2026)
Background: Basketball is a high-intensity intermittent sport that requires both aerobic and anaerobic energy systems. Physical demands vary across playing positions; however, evidence in adolescent players remains limited. Objectives: To compare aerobic and anaerobic capacities across different playing positions in basketball players aged 13-16 years Materials and methods: This cross-sectional study included 60 adolescent basketball players in Chiang Mai Province. Participants were categorized into five positional roles: point guard, shooting guard, small forward, power forward, and center. Aerobic capacity was assessed using estimated maximal oxygen consumption (VO₂max) from the 20-meter shuttle run test, while anaerobic capacity was evaluated using fatigue index (FI). The body composition variables were recorded, including body mass index, body fat percentage, and muscle mass percentage. Differences among groups were analyzed using one-way ANOVA with Bonferroni post hoc analysis. Results: No significant differences in anaerobic capacity (FI) were found among the five positions (p>0.05). In contrast, aerobic capacity (VO₂max) differed significantly between positions (p<0.05), with point guards demonstrating significantly higher VO₂max compared to centers. Other positional comparisons were not statistically significant. Conclusion: Aerobic capacity differed only between point guards and centers, with point guards demonstrating higher estimated VO₂max than centers, whereas anaerobic capacity appeared comparable across playing positions. These findings suggest that playing position may be associated with differences in aerobic performance and should be considered when designing training programs for adolescent basketball players.